2-(1H-indol-3-yl)-2 '-(1H-indol-3-yl-methylene)acetohydrazide - Ali, Hapipah Mohd; Ng, S.W.; Shimar, J.N. (International Union of Crystallography, 2007)
The molecules of the title compound, C19H16N4O, are linked into a three-dimensional architecture by N-H center dot center dot center dot O hydrogen bonds.